Are the Northland rivers of New Zealand in synchrony with global Holocene climate change? : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Geography at Massey University, Palmerston North, New Zealand - Richardson, Jane (Massey University, 2013)
Climate during the Holocene has not been stable, and with predictions of human induced climate change it has become increasingly important to understand the underlying ‘natural’ dynamics of the global climate system. Fluvial systems are sensitive respondents to and recorders of environmental change (including climate). This research integrates meta-data analysis of a New Zealand fluvial radiocarbon (14C) database with targeted research in catchments across the Northland region to determine the influence of Holocene climate change on river behaviour in New Zealand, and to assess whether or not Northland rivers are in synchrony with global climate change. The research incorporates 14C dating and meta-analysis techniques, sedimentology, geophysics, ground survey (RTK-dGPS) and Geographic Information Systems analysis to investigate the response of New Zealand and Northland rivers to Holocene climate and anthropogenic change. The emerging pattern of Holocene river behaviour in New Zealand is one of increased river activity in southern regions (South Island) in response to enhanced westerly atmospheric circulation (promoted by negative Southern Annular Mode [SAM]-like circulation), while in northern regions (North Island) river activity is enhanced by meridional atmospheric circulation (promoted by La Niña-like and positive SAM-like circulation). In Northland, Holocene floodplain development reflects the interplay between valley configuration and accommodation space, sediment supply, fluctuation in climate and anthropogenic factors in the last several hundred years. Evidence from Northland rivers suggests that a globally extensive abrupt climate change signal can promote a synchronous fluvial response, overprinting complex regional patterns of Holocene river behaviour. The research demonstrates that at the centennial-scale, regional atmospheric circulation change is a key driver of river behaviour, with anthropogenic catchment disturbance responsible for enhanced river activity and floodplain aggradation in the last ~ 500 years. It is therefore likely that any future climate change involving a shift in the atmospheric circulation regime will have an impact on river behaviour in New Zealand. However, at the catchment- or reach-scale, river response will be largely determined by local controls such as sediment supply and accommodation space, with these factors largely moderated by the post-settlement fluvial history.
Keywords: Paleolimnology; Paleoclimatology; Climatic changes; Rivers; Holocene; Climate change; New Zealand